Perancangan Boardgame Kartu Kakoru - Fernando Wijaya (LPPM STIKOM Tunas Bangsa, 2023)
Many young people especially Z Generation when they were bored with their activity along their friends, they choose to play their smartphone for their weariness relief. They also capable to adjust with the situation of recent technology development. These youngster also have characteristic that expressive and explorative, then it will not be a surprise for us when they are just more capable to do social media operating than the previous generation. Z Generation are easy to be bored because of their things which are commonly done by them as their regularly. Therefore, these generation need some, exciting, interesting and fun things for them. Next, to cope with their tendency to be bored, the writer decided to make Kakoru Card which has a series of activities, culinaries, and some attractive places in Surabaya. Not only that, to facilitate them exploring and expressing their creativity, this Kakoru Card provides barcode features which lead them to the Navigation and Kakoru’s Instagram Story Filter. So, the goal of creating Kokoru Card is to make Z Generation will have a willing to congregate with their friends by shuffling Kakoru Card and find the fun of being together again that is an exceptional thing these years.